1991
DOI: 10.1128/jb.173.13.4124-4132.1991
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of the tabtoxin biosynthetic region from Pseudomonas syringae

Abstract: Pseudomonas syringae BR2, a causal agent of bean wildfire, was subjected to Tn5 mutagenesis in an effort to isolate mutants unable to produce the I8-lactam antibiotic tabtoxin. Three of the tabtoxin-minus (Tox-) mutants generated appeared to have physically linked TnS insertions and retained their resistance to the active toxin form, tabtoxinine-,-lactam (T,IlL). The wild-type DNA corresponding to the mutated region was cloned and found to restore the TnS mutants to toxin production. The use of cloned DNA from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 41 publications
2
67
0
Order By: Relevance
“…2, both toxin production and toxin resistance were associated with the span of the region encompassing blocks II and III; this span also includes the prophage fragment that seems likely to be a vestigial remnant of a transfer event. Previous results had demonstrated that Tn5 insertions within the tabtoxin region resulted in the loss of toxin production without loss of host resistance to the antibiotic [5]. Sequence analysis confirms that the insertions in two of those mutants occurred in the tabC and tblS genes indicating that those two genes are required for antibiotic biosynthesis.…”
Section: Iv) Gene Cluster Blockmentioning
confidence: 56%
See 2 more Smart Citations
“…2, both toxin production and toxin resistance were associated with the span of the region encompassing blocks II and III; this span also includes the prophage fragment that seems likely to be a vestigial remnant of a transfer event. Previous results had demonstrated that Tn5 insertions within the tabtoxin region resulted in the loss of toxin production without loss of host resistance to the antibiotic [5]. Sequence analysis confirms that the insertions in two of those mutants occurred in the tabC and tblS genes indicating that those two genes are required for antibiotic biosynthesis.…”
Section: Iv) Gene Cluster Blockmentioning
confidence: 56%
“…2A) or that vector with the BamHI fragment insert (Fig. 2B), were inoculated into an M9 agar overlay and then challenged with a paper disk containing semipurified tabtoxin [5].…”
Section: Iv) Gene Cluster Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…syringae, coronatine (22,40) produced by P. syringae pv. tomato, and tabtoxin (15,38) produced by P. syringae pv. tabaci, have also been reported to be clustered.…”
Section: Discussionmentioning
confidence: 99%
“…Unkefer et al (40) suggested that the two pathways might diverge after L-dihydrodipicolinate (DHDPA). Reduction to L-2,3,4,5-tetrahydrodipicolinate (THDPA) by DapB (5) would lead to DAP, while hydration would place a hydroxyl group on the carbon that becomes carbon 5 of T␤L.All of the genes required for T␤L biosynthesis and resistance are located in a region of about 32 kb of the BR2 chromosome (19). Approximately 3 kb of that region has been sequenced, and two genes (tabA and tblA), essential for T␤L production but with unknown functions, have been identified.…”
mentioning
confidence: 99%